The Effect of Foreign Debt (ULN) And Foreign Investment (PMA) On Indonesia's Gross Domestic Product (GDP) in the Period (2012-2024) - Pamungkas, Giantoro; Prakoso, Riski Wisnu; Fahruqi, M. Nur (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Indonesia's economic growth remains a major challenge for the development of the country as the largest archipelagic country in the world. External factors such as Foreign Debt (ULN) and Foreign Direct Investment (PMA) are considered to influence Gross Domestic Product (GDP). This study aims to examine the influence of ULN and PMA on Indonesia's GDP in the period 2012-2024. Multiple regression analysis with the classical assumption test is used as a method in this study by conducting normality tests and hypothesis tests using t statistics and significance values. The results show that ULN has a positive effect with a significance of 0.000> α = 0.05 and a T-count value of 70.096 greater than the T-table of 2.034, which means that an increase in ULN can strengthen national economic development. Conversely, PMA does not show a significant effect on GDP in that period, indicated by a significance of 0.234> α = 0.05 and a T-count value of 1.212 less than the T-table of 2.034. Careful management of external debt can benefit the Indonesian economy, while the success of foreign investment requires greater attention to support optimal economic growth. This research underscores the importance of prudent economic policies in leveraging external factors to improve the welfare of the Indonesian people.